2014
DOI: 10.4238/2014.december.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the OLR1 3'UTR potential microRNA binding site and risk of Alzheimer’s disease: a meta-analysis

Abstract: ABSTRACT. Alzheimer's disease (AD) is a progressive neurodegenerative disorder that contributes to dementia in the elderly population. Genome-wide linkage analysis has identified chromosome 12p as the AD-susceptible region, which includes lectin-like oxidized low-density lipoprotein receptor 1 (OLR1). The OLR1 +1073 C/T single-nucleotide polymorphism is located in the 3'-untranslated region of the gene and may influence the binding of regulatory microRNAs (miRNAs) and OLR1 protein homeostasis. A number of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The one located in the pre-or pri-miRNA may compromise the generation of mature miRNA by interfering with the mature processing, undermining its secondary structure, or alternating the arm selection during the production of the miRNA (32). However, the variants in the UTR of the target genes may abolish or attenuate the inhibitory effect of miRNA on mRNA of the target by disrupting the binding or interaction between the miRNA and mRNA (33). KRAS 3'-UTR rs61764370 has been shown to be associated with some cancer phenotypes, such as prognosis in rectal cancer (34), and response to chemotherapy in colorectal cancer (35).…”
Section: Discussionmentioning
confidence: 99%
“…The one located in the pre-or pri-miRNA may compromise the generation of mature miRNA by interfering with the mature processing, undermining its secondary structure, or alternating the arm selection during the production of the miRNA (32). However, the variants in the UTR of the target genes may abolish or attenuate the inhibitory effect of miRNA on mRNA of the target by disrupting the binding or interaction between the miRNA and mRNA (33). KRAS 3'-UTR rs61764370 has been shown to be associated with some cancer phenotypes, such as prognosis in rectal cancer (34), and response to chemotherapy in colorectal cancer (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that miRNAs are directly related to AD. Dysregulation of miRNA profile is being investigated as a mechanism for AD pathogenesis by interrupting the metabolism of amino acids in the brain [13]. miR-153 has been shown to inhibit expression of APP in human neurons; low miR-153 levels may drive increased APP expression in a subset of AD patients [14].…”
Section: Genetics Of Admentioning
confidence: 99%
“…This was supported by two other studies (41,43). Recently, a meta-analysis including 2,419 cases and 2,381 controls from five studies demonstrated a significantly lower AD risk in the recessive model (TT vs. TC + CC: OR =0.79, 95% CI: 0.65-0.96), however, they failed to conduct further study to confirm the influence of APOEε4 on the association between rs1050283 polymorphism and AD (44). The results of an independent replication study by Pritchard et al provided support to our research (48), they performed an association study of rs1050283 in a UK population of 356 LOAD patients and 358 healthy controls, and failed to find any association between rs1050283 and AD, even after stratification by APOEε4 status, onset age and haplotype distributions.…”
Section: Discussionmentioning
confidence: 76%
“…However, the results are inconsistent (17,(40)(41)(42)(43). Recently, a metaanalysis confirmed the association of OLR1+1073 C/T with a decreased risk of AD among Caucasians (44). Moreover, Papassotiropoulos et al investigated a cluster of cholesterolrelated genes and identified rs1050286 polymorphism in OLR1 conferring significant susceptibility for AD (45).…”
Section: Introductionmentioning
confidence: 99%